The moderating role of openness to experience: Influence of nostalgia on purchase intention - Putra, Rahmat Eka; Fariz, Muhammad (Jurnal Kajian Manajemen Bisnis, 2020)
This study proposes and tests an interactional model of purchase intention where openness to experience serves as a core construct between nostalgia and purchase intention. Based on Identity Social Theory and the Big Five Model of personality traits, nostalgia and openness to experience are proposed as contextual and individual variables that are interrelated in this process. The interaction between openness to experience and nostalgia leads to buying intention behavior. In general, this model needs a moderation process where openness to experience is a crucial factor to transform the contextual resource into purchase intention behavior. The hypotheses are examined using structural Equation Modelling, based on data obtained from a self-administered survey of 273 respondents. We discuss the implication, both theoretical and practical in this study.Keywords: Nostlagia, Openness To Experience, purchase Intention, Social Identification Theory.Â